Lived experience of older adults with type 1 diabetes using closed‐loop automated insulin delivery in a randomised trial. Issue 4 (15th December 2022) - Kubilay, Erin; Trawley, Steven; Ward, Glenn M.; Fourlanos, Spiros; Grills, Charlotte A.; Lee, Melissa H.; MacIsaac, Richard J.; O'Neal, David N.; O'Regan, Niamh A.; Sundararajan, Vijaya; Vogrin, Sara; Colman, Peter G.; et al.
Abstract: Aim: To explore the lived experience of older adults with type 1 diabetes using closed‐loop automated insulin delivery, an area previously receiving minimal attention. Methods: Semi‐structured interviews were conducted with adults aged 60 years or older with long‐duration type 1 diabetes who participated in a randomised, open‐label, two‐stage crossover trial comparing first‐generation closed‐loop therapy (MiniMed 670G) versus sensor‐augmented pump therapy. Interview recordings were transcribed, thematically analysed and assessed. Results: Twenty‐one older adults participated in interviews after using closed‐loop therapy. Twenty were functionally independent, without frailty or major cognitive impairment; one was dependent on caregiver assistance, including for diabetes management. Quality of life benefits were identified, including improved sleep and reduced diabetes‐related psychological burden, in the context of experiencing improved glucose levels. Gaps between expectations and reality of closed‐loop therapy were also experienced, encountering disappointment amongst some participants. The cost was perceived as a barrier to continued closed‐loop access post‐trial. Usability issues were identified, such as disruptive overnight alarms and sensor inaccuracy. Conclusions: The lived experience of older adults without frailty or major cognitive impairment using first‐generation closed‐loop therapy was mainly positive and concordant with glycaemic benefits found in the trial. Older adults' lived experience using automated insulin delivery beyond trial environments requires exploration; moreover, the usability needs of older adults should be considered during future device development.